Micro–Nanostructure‐Assisted Luminescence in Perovskite Devices. Issue 12 (16th August 2021) - Tang, Ying-Yi; Shen, Yang; Wang, Jing-Kun; Qian, Xiao-Yan; Guo, Ming-Lei; Li, Yan-Qing; Tang, Jian-Xin
Abstract : Metal halide perovskite (MHP) materials have demonstrated great advantages over conventional semiconductors for the next‐generation optoelectronics on account of their outstanding photophysical properties and facile solution processability. Among all the related researches, the suitable micro–nanostructures have been proven to be a direct and effective optical and photophysical management strategy, which is essential for improving the luminescent characteristics of MHP‐based luminescent optoelectronics, including light‐emitting diodes (LEDs) and lasers. Herein, the developments of representative optical micro–nanostructures for perovskite luminescence with different architectures are first introduced, including metal nanoparticles, 1D Bragg gratings, 2D nanostructures with and without periodicity, and MHP nanocrystals. Notably, the fabrication techniques of various counterparts in micro–nanostructures are systematically reviewed. Moreover, the recent practical applications of micro–nanostructures in MHP‐based materials and luminescent optoelectronics are discussed in details, which mainly involves localized surface plasmon resonance (LSPR)‐derived luminescence improvement, optical outcoupling manipulation, and stimulated light emission via optical micro–nanocavity. Lastly, the challenges and perspectives for micro–nanostructures toward future's MHP‐based luminescence applications are summarized. Abstract : The recent developments of representative optical micro–nanostructures for perovskite luminescence are reviewed, including metal nanoparticles, 1D Bragg gratings, 2D nanostructures with and without periodicity, and perovskite nanocrystals. Their influence on luminescent optoelectronics has been discussed in terms of localized surface plasmon resonance‐derived luminescence improvement, optical outcoupling manipulation, and stimulated light emission via optical micro–nanocavity.